THE EFFECT OF GAMIFIED LEARNING METHOD ON STUDENTS THEMATIC LEARNING OUTCOMES IPS LOAD - Atika, Putri; Febrianto , Priyono Tri (Citra Dharma Cindekia, 2023)
The purpose of this study was to determine the effect of theGamified Learning method on student learning outcomes onsocial studies content, theme 7, sub-theme 3 class V atUPTD SDN Gili Barat, Kamal District, Bangkalan Regency.This study uses quantitative research methods with QuasiExperimental Design (pseudo-experimental) form of nonequivalent Control Group Design. The population in this studywere all students of class V UPTD SDN Gili Barat KamalBangkalan, totaling 43 students divided into classes V-A andV-B. The sampling technique used in this study is nonprobability sampling, saturated sampling. Data was collectedusing multiple choice test questions with a total of 20questions and observation. The results showed that theresults of statistical calculations using the IndependentSample T-Test formula (T test) at a significant level a = 0.05with the results of Tcount = 5,630 and Ttable = 2,020. Basedon the results of these calculations, Tcount ≥ Ttable then H0is rejected and Ha is accepted. So, the Gamified Learningmethod has a positive influence on student learningoutcomes.